Sustainable cities and local food systems : a partnership between restaurants and farms in Portland, Oregon - Taylor, Ashley Kaarina (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2009.